Red-Crowned Crane (Grus japonensis) Reproduction Was Improved by Inhibiting Mycotoxins with Montmorillonite in Feed - Liu, Dawei (Toxins (Basel), 2020)
The red-crowned crane (Grus japonensis) is a vulnerable bird species. Mycotoxins are toxic substances produced by filamentous fungi and are considered as naturally unavoidable contaminants in animal feed. Our recent survey indicated that feeds designed for captive red-crowned cranes were contaminated with mycotoxins. This study was conducted to investigate the protective effects of the mycotoxin binder montmorillonite on the reproductive behavior, sex hormone levels, and egg quality of red-crowned cranes. Twelve pairs of G. japonensis were divided into four groups, and each group was fed one of the following: a selected diet (with extra low levels of mycotoxins), a regular diet, a selected diet with 0.5% montmorillonite added, or a regular diet with 0.5% montmorillonite added. Consumption of the regular diet decreased courtship and mating behaviors, testosterone concentration, egg weight, and shell thickness. However, feed supplementation with montmorillonite increased the courtship, mating behaviors and testosterone concentration during the pre-breeding period, as well as egg weight and shell thickness. These findings suggest that the addition of dietary montmorillonite is effective for controlling mycotoxins in the feed, resulting in improvements in reproductive behaviors, testosterone concentrations, and some egg quality parameters of the red-crowned crane.